Child‐Turcotte‐Pugh versus MELD‐XI identify distinct high‐risk populations for heart transplantation following ventricular assist device placement. Issue 5 (26th February 2022) - Leven, Emily A.; Kurdi, Ahmed T.; Govindarajulu, Usha; Schiano, Thomas; Pinney, Sean; Crismale, James F.
Abstract: Background: Patients with end‐stage heart failure frequently have significant congestive hepatopathy requiring hepatology assessment prior to heart transplantation listing. An elevated Model for End‐stage Liver Disease score with modification to exclude INR (MELD‐XI) has been associated with increased mortality following heart transplantation (HT). This study's primary aim was to examine whether Child‐Turcotte‐Pugh (CTP) classification is associated with post‐transplant mortality in patients bridged to transplant with left ventricular assist devices. Methods and Results: We conducted a retrospective analysis of 134 patients from our center. Age, CTP class, and MELD‐XI at HT were included in the multivariate model for the primary outcome, which demonstrated a significant association between 1‐year mortality and CTP class (CTP‐A HR: .08, CI .01–.46, P < .01; CTP‐B HR: .25, CI .05–1.2, P = .08; reference group CTP‐C), and MELD‐XI (HR: 1.15; CI: 1.03–1.28; P = .01), but no significant difference for age (HR: .97; CI: .93–1.01; P = .15). Only 13/33 patients with CTP improvement after assist device also had improvement in MELD‐XI. Conclusions: Patients with relatively low MELD‐XI scores with discordantly high CTP classification may be a distinct subset for whom MELD‐XI underestimates the risk of mortality after heart transplantation compared to CTP.